Transition metal Fe in-situ doped C3N5 photocatalyst and preparation method and application thereof

The Fe-C3N5 photocatalyst is formed by Fe in situ doping C3N5, which solves the problems of low solar light utilization efficiency and limited carrier recombination of existing photocatalysts, and achieves efficient degradation and environmentally friendly treatment effects of antibiotics.

CN119680601APending Publication Date: 2025-03-25CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411784081.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing photocatalysts are inefficient in utilizing sunlight, and are limited by carrier recombination and lack of active sites, making it difficult to effectively degrade residual antibiotics in medical wastewater.

Method used

By in situ doping the transition metal Fe into C3N5, a Fe-C3N5 photocatalyst is formed, and the heterogeneous activated persulfate of Fe is used to generate sulfate radicals, thereby improving the photocatalytic degradation efficiency.

Benefits of technology

It significantly improves the visible light utilization efficiency and stability of the photocatalyst, shortens the time for photocatalytic degradation of antibiotics, and reduces the risk of secondary pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680601A_ABST
    Figure CN119680601A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a transition metal Fe-doped C3N5 photocatalytic material and application of the transition metal Fe-doped C3N5 photocatalytic material in the aspect of photocatalytic degradation of antibiotics in cooperation with persulfate. The material is synthesized by a one-step calcination method, a Fe-C3N5 photocatalyst with good Fe dispersibility is formed by a double-layer nitrogen matrix co-derived from FeCl3. 6H2O and a C3N5 nitrogen-rich precursor which are easy to obtain raw materials, rich active sites are provided for PMS activation, and the stability of the catalyst can be improved by the double-layer nitrogen structure. The forbidden band width value of Fe-C3N5 is as low as 1.62 eV, and the recombination rate of photo-induced electrons and holes is remarkably reduced. Under the condition of a 50W LED white lamp light source with a wavelength range of 400 nm to 830 nm and light intensity controlled at 10000 Lux, when the material dosage is 0.4 g / L and the PMS dosage is 10 mg, the degradation rate of 20 mg / L antibiotic aureomycin within 120 min reaches 95% or above. Therefore, the photocatalyst can effectively activate PMS under the condition of visible light irradiation and rapidly degrade organic pollutants, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of photocatalysis and relates to a preparation method for synthesizing a transition metal Fe in-situ doped C3N5 photocatalyst and its application in degrading antibiotics in wastewater. Technical background:

[0002] Medical wastewater contains a variety of antibiotics, which persist after treatment using traditional methods such as physical adsorption, biological treatment, membrane filtration, advanced oxidation and ion exchange. The presence of residual antibiotics in the environment remains a prominent problem due to their potential hazards, toxic effects and persistence. Therefore, there is an urgent need to develop green and efficient wastewater treatment processes to degrade residual antibiotics in medical wastewater.

[0003] At present, photocatalytic oxidation synergistic persulfate advanced oxidation technology has attracted much attention due to its advantages such as simple operation and mild reaction conditions. Compared with traditional advanced oxidation technology, photocatalytic oxidation synergistic persulfate advanced oxidation technology can produce sulfate radicals with stronger oxidizing properties than hydroxyl radicals, and can work effectively in a wider pH range, with low toxicity and higher stability. However, traditional photocatalysts such as TiO2, BiVO4, and C3N4 use ultraviolet light as the light source, fail to fully utilize sunlight, and are limited by their own high photogenerated electron-hole recombination rate, resulting in poor photocatalytic effects and hindering the practical application of photocatalytic technology. If we want to fully utilize sunlight, the development of photocatalytic materials with high photocatalytic activity and good stability in visible light response is the key to realizing the industrial application of photocatalytic technology.

[0004] Nitrogen-rich graphitic carbon nitride (C3N5) is a new type of semiconductor photocatalyst that has attracted widespread attention due to its catalytic properties under visible light, low band gap and excellent thermal stability. However, C3N5 also has inherent defects such as carrier recombination and lack of active sites, which limits its photocatalytic ability and further application.

[0005] In order to solve the above problems, people have developed metal element doped modified photocatalysts. By modifying the photocatalyst with heteroatoms, the physical and chemical properties of the photocatalyst can be changed, so that it has good photoelectrochemical performance. The transition metal Fe can produce sulfate radicals through heterogeneous activation of persulfate, which can achieve efficient degradation of organic pollutants. The nitrogen-rich site of C3N5 has a strong electronegativity and is easy to combine with positively charged iron ions. The transition metal Fe with unoccupied d orbitals can act as an electron donor or acceptor, and it is easy to form a complex with C3N5 through electron transfer. Fe-doped C3N5 as an efficient photocatalyst has attracted more and more attention due to its wide availability, low cost, good stability and low metal ion leaching rate.

[0006] Liu JJ, Zhao CC, Zheng JT, et al. Efficiently photocatalysis activation of peroxydisulfate by Fe-doped g-C3N5 for pharmaceuticals and personal care products degradation[J]. ENVIRONMENTAL POLLUTION, 2023, 322. A method for preparing C3N5 doped with ferric chloride hexahydrate is disclosed, specifically, C3N5 is first dispersed in ethanol, FeCl3·6H2O is dissolved in deionized water, and then the FeCl3 solution is added to the C3N5 dispersion and stirred, and then washed and dried. After calcination in a tubular furnace, the material is immersed in an HCl solution to remove uncoordinated iron ions, and then washed with deionized water and dried to obtain Fe-doped C3N5 photocatalytic material with a band gap value of 1.53 eV. At 100 mW / cm 2 Under the irradiation of simulated sunlight, the degradation rate of tetracycline hydrochloride by activated PDS at pH = 3 was 66% within 60 minutes, and the degradation rate of naproxen at pH = 7 was 55%.

[0007] Shen W, Li Y, Shen C, et al. Enhancing the photo-Fenton catalytic activity of g-C3N5 under visible light through Z-scheme heterojunction with ferric iron [J]. Journal of Materials Research, 2023, 38 (10): 2775-2786. The method is to synthesize Fe / CN-a by calcination, specifically, ammonium acetate is added to ethanol, then C3N5 is added, and the mixture is poured into an autoclave and heated. The FeCl3 aqueous solution is added to ethanol, mixed with the above reaction mixture, and the product is washed with ethanol after stirring, and then heated in a muffle furnace, and naturally cooled to room temperature to obtain a brown product Fe / CN-a. The solvothermal method synthesizes Fe / CN-b, specifically, the FeCl3 aqueous solution and ammonium acetate are added to ethanol respectively, and then C3N5 is dispersed into the solution, and then the mixture is placed in an autoclave for solvothermal reaction. After naturally cooling to room temperature, the product is washed with ethanol and dried to obtain a dark brown product Fe / CN-b. The band gap value of Fe / CN-a is 2.15eV, and the band gap value of Fe / CN-b is 2.07eV. Using a 250W Xe lamp with a 420nm cut-off filter to simulate visible light, the degradation rate of methyl orange by Fe / CN-a activated H2O2 reached 100% within 100min, and the degradation rate of methylene blue by Fe / CN-b activated H2O2 reached 100%.

[0008] Lv W,Cao H,Guan Y,et al.Mediating peroxymonosulfate activation pathin Fenton-like reaction via doping different metal atoms into g-C3N5[J].Journal of Colloid and Interface Science,2024,674:416-427. A method for preparing C3N5 doped with heptahydrate ferrous sulfide is disclosed. Specifically, 3-amino-1,2,4-triazole and FeSO4·7H2O are uniformly mixed in an aqueous solution, the solid powder is heated at 90°C to evaporate the water, and then annealed at 550°C for 2h at a heating rate of 5.0°C / min in a N2 atmosphere to obtain Fe-C3N5 with a band gap value of 1.46eV. Under the condition of pH=7, the degradation rate of tetracycline hydrochloride by activated PMS within 60min is 80.7%.

[0009] The publication number is CN115155589B. A photocatalyst capable of activating sulfite to degrade tetracycline and its preparation method and application: C3N5 is dissolved in a sodium sulfide solution, and FeCl3 solution is added and ultrasonicated to obtain a solid-liquid mixture. The solid-liquid mixture is reacted by a one-pot hydrothermal method to obtain a FeS2 and C3N5 composite material. Under a xenon lamp with a 400nm cutoff filter, the catalyst has a tetracycline degradation rate of about 75% within 60 minutes.

[0010] Publication No. CN117339632A A MOFs-Co induced derivatization Co doped C3N5 photocatalyst and preparation method and application: The material is synthesized by solvothermal method and calcination method, and a double-layer nitrogen matrix is ​​derived from the MOFs-Co ligand skeleton and the C3N5 nitrogen-rich precursor to form a MOFs-Co-C3N5 photocatalyst with good Co dispersion. The catalyst completely degrades chlortetracycline within 6 minutes, but it is necessary to prepare the MOFs-Co material first and then calcine it at high temperature. Its preparation process is complicated and the economic cost is high, which does not conform to the concept of green and low-carbon development.

[0011] The reported Fe-doped C3N5 photocatalysts are all prepared by first preparing C3N5, and then loading it onto C3N5 through iron salt as the iron source. These catalysts basically have the defects of low visible light utilization, high electron-hole recombination rate, non-dispersed active sites, low degradation efficiency, unstable catalyst structure, poor Fe dispersibility, and complex preparation process. Therefore, the present invention proposes to use transition metal Fe to be in-situ doped into C3N5 by one-step calcination, because it has highly dispersed metal sites that are conducive to activating PMS and improving its efficiency of photocatalytic degradation of organic pollutants. The Fe-doped C3N5 material prepared by this method can significantly reduce the bandgap value and the recombination rate of photogenerated electrons-holes, improve the utilization efficiency of actual visible light, and the rich mesoporous structure is conducive to shortening the time of photocatalytic degradation of organic pollutants such as antibiotics. Summary of the invention:

[0012] The purpose of the invention is to provide a transition metal Fe in-situ doped C3N5 photocatalyst and a preparation method, as well as the application of the material in the photocatalytic degradation of organic pollutants in water.

[0013] To achieve the above object, the present invention adopts the following technical solution:

[0014] 1. Mix the mixture consisting of iron salt, nitrogen-rich compound and six-membered nitrogen heterocycle evenly under heating, dry, grind the obtained solid substance into powder, and calcine at high temperature to obtain Fe-C3N5 photocatalyst;

[0015] a. The mixture mainly includes a nitrogen-rich compound: 3-amino-1,2,4-triazole, the six-membered nitrogen heterocycle is at least one of cyanuric acid and barbituric acid, and the iron salt is FeCl3·6H2O;

[0016] b. Mix FeCl3·6H2O and the mixture: First, add an organic solvent to FeCl3·6H2O and the mixture, stir and ultrasonicate, then put the mixture into an oven at 70°C until the solution is completely evaporated, and grind it into powder in a mortar;

[0017] c. The mixed powder is placed in an alumina crucible with a lid, and then placed in a tube furnace and heated at 500°C to 550°C for more than 3 hours at a maximum heating rate of 5°C / min, and then taken out after cooling to room temperature, washed, and dried to obtain a Fe-C3N5 photocatalyst. The calcination is carried out in an inert gas atmosphere, preferably argon.

[0018] In a specific embodiment, the method further includes adding the fully mixed powder in step a to an auxiliary agent solution, stirring, and then drying, and then performing step b on the dried powder; the auxiliary agent is a potassium salt, and the potassium salt is preferably at least one of potassium bromide, potassium chloride or potassium iodide, and the mass ratio of the auxiliary agent to the mixed powder is preferably 0 to 4%.

[0019] In a specific embodiment, the method further comprises step b wherein the organic solvent is anhydrous ethanol in an amount of 100 ml.

[0020] In a specific embodiment, the method further comprises step b, wherein the stirring is performed at 80° C. for a time greater than 2 h, and the ultrasonication is performed for a time greater than 1 h.

[0021] In a specific embodiment, the mass ratio of the FeCl3·6H2O to the mixed material is 0.001 to 0.1:1, preferably 0.125 to 0.75:1.

[0022] Application of the above transition metal Fe in-situ doped C3N5 photocatalytic material in the degradation of organic pollutants:

[0023] Step 1: adding Fe-C3N5 into wastewater containing organic matter to obtain a mixed solution;

[0024] Step 2: adding persulfate to the mixed solution obtained in step 1 to obtain a mixed solution containing a catalyst and an oxidant;

[0025] Step 3: react the mixed solution obtained in step 2 under visible light for 5 to 120 minutes.

[0026] The addition amount of the above-mentioned Fe-C3N5 is 0.4g / L.

[0027] The above-mentioned target organic pollutant is the antibiotic chlortetracycline (CTC).

[0028] The pH of the reaction system is 3-11, and the reaction system is suitable for treating organic pollutants in wastewater with concentrations of chloride ions, carbonates, nitrates and bicarbonates below 10 mM.

[0029] Compared with the prior art, the present invention has the following advantages and effects:

[0030] (1) The material described in this patent is a double-layer nitrogen structure formed by co-deriving the metal element Fe and the C3N5 nitrogen-rich precursor, which can improve the stability of the catalyst, effectively solve the Fe dispersion problem, avoid the Fe ion leaching problem, and avoid secondary pollution to the environment.

[0031] (2) Compared with the traditional C3N5 photocatalyst, the FeCl3·6H2O prepared in the present invention has higher separation efficiency of photogenerated carriers, more reaction active sites, and stronger photocatalytic activity.

[0032] (3) The activated persulfate of FeCl3·6H2O prepared by the present invention can react quickly at room temperature and pressure to treat organic pollutants, with low energy consumption and simple operation. Compared with other catalysts, it has the characteristics of fast free radical generation rate, shortened reaction time to less than 10 minutes, and high pollutant degradation efficiency.

[0033] (4) The FeCl3·6H2O activated persulfate prepared by the present invention is less affected by the environment in treating organic pollutants and can degrade organic pollutants such as chlortetracycline in the pH range of 3 to 11. The reaction system is suitable for treating various complex water pollutants. Description of the drawings:

[0034] Figure 1 XRD diagrams of Examples 1, 2, 3, 4, and 5 of the present invention;

[0035] Figure 2 FTIR images of Examples 1, 2, 3, 4, and 5 of the present invention;

[0036] Figure 3 SEM images of Examples 1, 2, 3, 4 and 5 of the present invention; Figure a is Fe-C3N5 (12.5%), Figure b is Fe-C3N5 (25%), Figure c is Fe-C3N5 (50%), Figure d is Fe-C3N5 (62.5%), Figure e is Fe-C3N5 (75%), and Figure f is Fe-C3N5 (50%) after use;

[0037] Figure 4 The pore size distribution curve of Fe-C3N5 (50%) after use in Example 3;

[0038] Figure 5 The UV-visible diffuse reflection absorption spectra of Examples 1, 2, 3, 4, and 5 of the present invention;

[0039] Figure 6 Graphs showing band gap widths of embodiments 1, 2, 3, 4, and 5 of the present invention;

[0040] Figure 7 It is a comparison diagram of electrochemical impedance spectra of Example 3 and original C3N5 without iron doping;

[0041] Figure 8 A comparison diagram of Example 3 and the original C3N5 Mott-Schottky without iron doping;

[0042] Fig. 9 This is a graph showing the efficiency of Fe-C3N5 (50%) activating persulfate to degrade chlortetracycline in the test example;

[0043] Fig.10 This is a comparison chart of the effect of Fe-C3N5 (50%) on CTC degradation efficiency under different PMS dosage conditions in the test example;

[0044] Fig.11 This is a comparison chart of the effect of Fe-C3N5 (50%) on CTC degradation efficiency under different pH conditions in the test example;

[0045] Fig.12 This is a comparison chart of the effect of Fe-C3N5 (50%) on CTC degradation efficiency under different CTC concentration conditions in the test example;

[0046] Fig.13 This is a comparison chart of the effect of Fe-C3N5 (50%) on CTC degradation efficiency under different interfering ion conditions in the test example;

[0047] Fig.14 This is a comparison chart of the degradation efficiency of Fe-C3N5 (50%) after four cycles of use under the same conditions in the test example;

[0048] Fig.15 FTIR comparison chart of Fe-C3N5 (50%) before and after use in the test example;

[0049] Fig.16 This is a graph showing the results of the test example of Fe-C3N5 (50%) activating persulfate to degrade CTC in different water bodies;

[0050] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0051] Example 1

[0052] This example provides a preparation method of Fe-C3N5 (12.5%) transition metal Fe in-situ doped C3N5 photocatalyst, the specific steps are as follows:

[0053] 1) Synthesis of Fe-C3N5 (12.5%) precursor: 4.5 g 3-amino-1,2,4-triazole, 4.5 g cyanuric acid, 0.3 g barbituric acid, 0.3 g KBr, and 0.5625 g FeCl3·6H2O were dissolved in 100 mL anhydrous ethanol, stirred for 2 h, ultrasonicated for 1 h, mixed and dried, and ground into powder in an agate mortar to obtain Fe-C3N5 (12.5%) precursor;

[0054] 2) Preparation of Fe-C3N5 (12.5%): The powder obtained above was transferred into a 20 mL alumina crucible and transferred into a tube furnace. The temperature was increased to 500°C at a rate of 5 min / °C and kept for 3 h. The mixture was then cooled to room temperature and ground into powder in a mortar. The impurities were washed away with deionized water and dried at 80°C to obtain brown powder Fe-C3N5 (12.5%).

[0055] Example 2

[0056] This example provides a method for preparing Fe-C3N5 (25%) transition metal Fe in-situ doped C3N5 photocatalyst, the specific steps are as follows:

[0057] 1) Synthesis of Fe-C3N5 (25%) precursor: 4.5 g 3-amino-1,2,4-triazole, 4.5 g cyanuric acid, 0.3 g barbituric acid, 0.3 g KBr, and 1.125 g FeCl3·6H2O were dissolved in 100 mL anhydrous ethanol, stirred for 2 h, ultrasonicated for 1 h, dried after mixing, and ground into powder in an agate mortar to obtain Fe-C3N5 (25%) precursor;

[0058] 2) Preparation of Fe-C3N5 (25%): The powder obtained above was transferred into a 20 mL alumina crucible and transferred into a tube furnace. The temperature was increased to 500°C at a rate of 5 min / °C and kept for 3 h. The mixture was then cooled to room temperature and ground into powder using an agate mortar. The powder was washed with deionized water to remove impurities and dried at 80°C to obtain brown powder Fe-C3N5 (25%).

[0059] Example 3

[0060] This example provides a method for preparing Fe-C3N5 (50%) transition metal Fe in-situ doped C3N5 photocatalyst, the specific steps are as follows:

[0061] 1) Synthesis of Fe-C3N5 (50%) precursor: 4.5 g 3-amino-1,2,4-triazole, 4.5 g cyanuric acid, 0.3 g barbituric acid, 0.3 g KBr, and 2.25 g FeCl3·6H2O were dissolved in 100 mL anhydrous ethanol, stirred for 2 h, ultrasonicated for 1 h, dried after mixing, and ground into powder in a mortar to obtain Fe-C3N5 (50%) precursor;

[0062] 2) Preparation of Fe-C3N5 (50%): The powder obtained above was transferred into a 20 mL alumina crucible and transferred into a tube furnace. The temperature was increased to 500°C at a rate of 5 min / °C and kept for 3 h. The mixture was then cooled to room temperature and ground into powder using an agate mortar. The powder was washed with deionized water to remove impurities and dried at 80°C to obtain brown powder Fe-C3N5 (50%).

[0063] Example 4

[0064] This example provides a preparation method of Fe-C3N5 (62.5%) transition metal Fe in-situ doped C3N5 photocatalyst, the specific steps are as follows:

[0065] 1) Synthesis of Fe-C3N5 (62.5%) precursor: 4.5 g 3-amino-1,2,4-triazole, 4.5 g cyanuric acid, 0.3 g barbituric acid, 0.3 g KBr, and 2.8125 g FeCl3·6H2O were dissolved in 100 mL anhydrous ethanol, stirred for 2 h, ultrasonicated for 1 h, mixed and dried, and ground into powder in an agate mortar to obtain Fe-C3N5 (62.5%) precursor;

[0066] 2) Preparation of Fe-C3N5 (62.5%): The powder obtained above was transferred to a 20 mL alumina crucible and transferred to a tube furnace. The temperature was increased to 500°C at a rate of 5 min / °C and kept for 3 h. The mixture was then cooled to room temperature and ground into powder using an agate mortar. The powder was washed with deionized water to remove impurities and dried at 80°C to obtain brown powder Fe-C3N5 (62.5%).

[0067] Example 5

[0068] This example provides a preparation method of Fe-C3N5 (75%) transition metal Fe in-situ doped C3N5 photocatalyst, the specific steps are as follows:

[0069] 1) Synthesis of Fe-C3N5 (75%) precursor: 4.5 g 3-amino-1,2,4-triazole, 4.5 g cyanuric acid, 0.3 g barbituric acid, 0.3 g KBr, and 3.375 g FeCl3·6H2O were dissolved in 100 mL anhydrous ethanol, stirred for 2 h, ultrasonicated for 1 h, dried after mixing, and ground into powder in an agate mortar to obtain Fe-C3N5 (75%) precursor;

[0070] 2) Preparation of Fe-C3N5 (75%): The powder obtained above was transferred into a 20 mL alumina crucible and transferred into a tube furnace. The temperature was increased to 500°C at a rate of 5 min / °C and kept for 3 h. The mixture was then cooled to room temperature and ground into powder using an agate mortar. The powder was washed with deionized water to remove impurities and dried at 80°C to obtain brown powder Fe-C3N5 (75%).

[0071] The XRD patterns of the materials obtained in Examples 1, 2, 3, 4 and 5 are as follows: Figure 1 As shown. The example shows no new peaks and typical carbon nitride diffraction peaks, indicating that the transition metal Fe does not destroy the original structure of C3N5. The peak intensity of the doped sample is weaker than that of C3N5, indicating that the combination of metal elements and triazole ring structure can lead to a decrease in the crystallinity of the material and a decrease in the grain size. With the increase of FeCl3·6H2O doping amount, the characteristic peak moves to a higher angle and the peak intensity gradually weakens, indicating that the degree of graphitization is weakened, the conductivity is reduced, and the charge separation efficiency is reduced.

[0072] The FTIR of the materials obtained in Examples 1, 2, 3, 4, and 5 is as follows Figure 2 As shown in the figure, there is no obvious difference between the FTIR spectra of doped samples and undoped samples, which indicates that trace Fe ion doping does not change the chemical structure of C3N5. -1 It weakens with the further increase of Fe doping amount, indicating that the -NH groups on the catalyst surface may be important sites for bonding with Fe, which is beneficial to the improvement of catalyst performance.

[0073] The SEM images of the materials obtained in Examples 1, 2, 3, 4, and 5 are as follows: Figure 3As shown, all photocatalysts present similar porous morphology structures, but the pore structures of Examples 1, 2, 4, and 5 are not uniform, and there is overlap between the micropores. This overlapping structure makes the active site exposure of the photocatalyst low, and the contact with the reactants during the degradation process is subject to certain restrictions, affecting its photocatalytic performance. From the SEM spectrum of Example 3, it can be observed that the pores of the photocatalyst are clear and large in number, presenting a porous structure, which is conducive to the absorption of visible light and provides more reaction sites, thereby making the photocatalytic performance of the photocatalyst better. As can be seen from Figure (f), Fe-C3N5 (50%) still maintains a porous structure after the reaction, proving the stability of the photocatalyst.

[0074] The pore size distribution curve of the material obtained in Example 3 is as follows Figure 4 As shown, the results show that Fe-C3N5 (50%) has a rich mesoporous structure, which can provide more active sites for photocatalytic degradation of chlortetracycline and is beneficial to the activation of PMS. The Fe-C3N5 (50%) after use was not destroyed by the reaction, indicating that the catalyst structure is stable.

[0075] The UV-visible diffuse reflection absorption spectra and band gap widths of the materials obtained in Examples 1, 2, 3, 4, and 5 are as follows: Figure 5 , 6 shown. Figure 5 It shows the light absorption ability of the material between 300 and 800nm. The absorption wavelength threshold of all samples can be extended to the visible light region. When the absorption wavelength is in the range of 400 to 800nm, all samples have strong absorption. Figure 6 According to the Kubelka-Munk function, the band gap value of Fe-C3N5 (12.5%) is 1.64eV, the band gap value of Fe-C3N5 (25%) is 1.63eV, the band gap value of Fe-C3N5 (50%) is 1.63eV, the band gap value of Fe-C3N5 (62.5%) is 1.62eV, and the band gap value of Fe-C3N5 (75%) is 1.62eV. The above results all show that Fe doping can adjust the band structure of C3N5, making Fe-C3N5 have a stronger visible light response, thereby achieving a better photocatalytic effect.

[0076] Figure 7 To perform EIS analysis on the undoped sample and Fe-C3N5 (50%) under dark conditions. The arc radius of Fe-C3N5 (50%) is significantly smaller than that of the undoped C3N5 sample, indicating that the photoelectrochemical performance of Fe-C3N5 (50%) has been enhanced; similarly, Figure 8The Mott-Schottky curves of the above samples are positive, indicating that they are all N-type semiconductors. The above electrochemical tests show that the introduction of Fe under light induction can exert a certain resistance to charge separation and photogenerated electron transfer, thereby enhancing charge separation and transfer, which is beneficial to improving photocatalytic activity.

[0077] Test and results: The method for investigating the photocatalytic activity of the material provided by the present invention is as follows:

[0078] The above catalyst (0.01-0.04 g) was added to 50 mL of 10 mg / L chlortetracycline solution and stirred at 450 rpm / min in the dark for 30 min until the photocatalytic material reached adsorption equilibrium. After adding PMS, the solution was placed under a 50W LED white light source of 10000 Lux to conduct a photocatalytic degradation experiment of pollutants, and samples were taken regularly and filtered (0.22 μm pore size filter membrane) to measure the chlortetracycline concentration at 366 nm by UV-visible spectrophotometer.

[0079] Test Example

[0080] Take 20mg of Fe-C3N5 (50%) to 50mL of 10mg / L chlortetracycline solution, stir at 450rpm / min in the dark for 30min until the photocatalytic material reaches adsorption equilibrium. After adding PMS, place the solution under 10000Lux 50W LED white light source to carry out photocatalytic degradation experiment of pollutants, and regularly sample and filter (0.22μm pore size filter membrane) to measure the chlortetracycline concentration by UV-visible spectrophotometer.

[0081] Table 1 Effect of dosage on degradation rate in test example 3

[0082]

[0083] Fig. 9 The degradation rate of CTC increased from 79.85% to 83.78% within 120 minutes when the catalyst dosage increased from 10mg to 20mg. This is because the active sites involved in PMS activation increased with the increase in catalyst dosage. However, when the catalyst dosage increased to 40mg, the degradation rate decreased. This is because excessive catalyst dosage will increase the concentration of suspended particles in the solution, scatter the incident light, block the penetration of light, reduce the utilization rate of the light source, and reduce the generation of photogenerated carriers, which affects the activation of PMS to oxidize and degrade CTC. Therefore, the optimal catalyst dosage is determined to be 20mg.

[0084] Table 2 shows the degradation of chlortetracycline by Fe-C3N5 (50%) at different PMS dosages, different pH values ​​and different chlortetracycline concentrations.

[0085]

[0086]

[0087] Fig.10 The degradation effects of CTC under the conditions of 5 mg, 10 mg, 15 mg and 20 mg of PMS dosage in Test Example 3 were compared. The results showed that the degradation rate of Fe-C3N5 (50%) photocatalytic material at a PMS dosage of 15 mg was only 0.21% higher than that at a PMS dosage of 10 mg. Considering the economic cost of the material, 10 mg was selected as the optimal PMS dosage. Fig.11 The degradation effects of different pH on CTC in Test Example 3 were compared under the conditions of 20 mg of Fe-C3N5 (50%) and 10 mg of PMS. The results showed that Fe-C3N5 (50%) had a higher degradation effect on CTC within the pH range studied, and the adaptable pH range was wider. In particular, the degradation effect of CTC under neutral and weakly acidic conditions was significantly improved. Under the condition of pH 11, the degradation rate of CTC became lower. This is because chlortetracycline will undergo a ring-opening reaction under strong alkaline conditions, resulting in the destruction of the four-ring structure and the formation of isochlortetracycline. Fig.12 The degradation effects of different CTC concentrations in Test Example 3 were compared under the conditions of PMS dosage of 10 mg and pH of 5. The results showed that the degradation effect of Fe-C3N5 (50%) photocatalytic material on chlortetracycline could reach more than 95% within 120 minutes when the CTC concentration was 20 mg / L. Fig.13 The effects of different interfering ions on the degradation of chlortetracycline under the conditions of PMS dosage of 10 mg and pH of 5 in Test Example 3 were compared. Sodium chloride, sodium bicarbonate, sodium nitrate, sodium sulfate and sodium dihydrogen phosphate were added to simulate the degradation of chlortetracycline. - 、HCO3 - 、NO3 - 、SO4 2- and HPO4 2- Regarding the effect on CTC degradation efficiency, when the amount of coexisting ions added was set to 10 mM, the results showed that hydrogen phosphate could significantly promote the degradation of CTC, while the other coexisting ions had no obvious inhibitory effect on CTC, indicating that the system has strong anti-interference ability.

[0088] Fig.14 The test examples were compared and subjected to four degradation cycles under the same experimental conditions to examine the reusability and stability of the catalyst in practical applications. As shown in the figure, the removal efficiency of the fourth cycle experiment decreased by about 7.0% compared with the results of the first cycle, which may be due to the Fe2+ It is continuously consumed during the cyclic reaction, resulting in Fe 3+ The reduction performance weakened and the degradation rate decreased. The infrared spectrum of the used Fe-C3N5 (50%) matches well with the infrared spectrum of the unused Fe-C3N5 (50%) ( Fig.15 ), indicating that the surface functional groups of the material have no obvious changes and have good structural and compositional stability.

[0089] Table 3 Degradation of chlortetracycline by Fe-C3N5 (50%) under different water conditions.

[0090]

[0091]

[0092] Fig.16 The removal efficiency of CTC in different aqueous solutions over time is shown, revealing the stability of Fe-C3N5 (50%) catalyst in degrading pollutants in different water environments. Fig.16 As shown, no matter in the campus Dongfeng Canal water, Yanhu water or tap water, the photocatalytic efficiency of Fe-C3N5 (50%) catalyst for CTC under the activation of PMS can reach more than 75% within 120 minutes, and according to the dark reaction adsorption stage, it can also be concluded that the Fe-C3N5 (50%) / PMS / CTC system has better performance in water bodies with more complex compositions, indicating that the in-situ doping of C3N5 material with transition metal Fe is beneficial to the activation of PMS due to its highly dispersed metal sites, thereby improving its efficiency in photocatalytic degradation of organic pollutants, and has important application value for the treatment of pollutants in actual complex water bodies.

Claims

1. A method for preparing a C3N5 photocatalytic material in situ doped with transition metal Fe, characterized in that: The following steps are involved: The mixture consisting of iron salt, nitrogen-rich compound and six-membered nitrogen heterocyclic ring is mixed uniformly under heating, dried, and the obtained solid material is ground into powder and calcined at high temperature to obtain Fe-C3N5 photocatalyst; a. The mixture mainly includes a nitrogen-rich compound: 3-amino-1,2,4-triazole, the six-membered nitrogen heterocycle is at least one of cyanuric acid and barbituric acid, and the iron salt is FeCl3·6H2O; b. Mix FeCl3·6H2O and the mixture: First, add an organic solvent to FeCl3·6H2O and the mixture, stir and ultrasonicate, then put the mixture into an oven at 70°C until the solution is completely evaporated, and grind it into powder in a mortar; c. Place the mixed powder into an alumina crucible with a lid, move it into a tube furnace and keep it at 500°C to 550°C for more than 3 hours at a maximum heating rate of 5°C / min. After cooling to room temperature, take it out, wash it, and dry it to obtain a Fe-C3N5 photocatalyst. The calcination is carried out under an inert gas atmosphere, preferably argon.

2. The method for preparing the Fe-C3N5 photocatalyst according to claim 1, characterized in that: The iron salt is selected as FeCl3·6H2O.

3. The method for preparing the Fe-C3N5 photocatalyst according to claim 1, characterized in that: The method further comprises adding the powder mixed thoroughly in step a to an auxiliary agent solution, stirring and drying, and then subjecting the dried powder to step b; the auxiliary agent is a potassium salt, and the potassium salt is preferably at least one of potassium bromide, potassium chloride or potassium iodide, and the organic solvent is anhydrous ethanol.

4. The method for preparing the Fe-C3N5 photocatalyst according to claim 3, characterized in that: The stirring time at room temperature is greater than 2 hours, and the ultrasonic time is greater than 1 hour.

5. The method for preparing a Fe-C3N5 photocatalyst according to claim 1 or 2, characterized in that: The FeCl3·6H2O The ratio to the mixed material mass is 12.5-75%.

6. A method for preparing a Fe-C3N5 photocatalyst, characterized in that: The Fe-C3N5 photocatalyst is prepared by the method described in any one of claims 1 to 6.

7. The use of the Fe-C3N5 photocatalyst in degrading organic pollutants in claim 6, characterized in that: Step 1: adding Fe-C3N5 into wastewater containing organic matter to obtain a mixed solution; Step 2: adding persulfate to the mixed solution obtained in step 1 to obtain a mixed solution containing a catalyst and an oxidant; Step 3: react the mixed solution obtained in step 2 under visible light for 5 to 120 minutes.

8. The use according to claim 6, characterized in that: The Fe-C3N5 is selected from Fe-C3N5 (50%), and the addition amount of the material is 0.1-0.4g / L.

9. The use according to claim 8, characterized in that: The organic pollutant is chlortetracycline (CTC).

10. The use according to claim 8, characterized in that: The pH of the reaction system is 3-11, and the reaction system is suitable for treating organic pollutants in wastewater with concentrations of chloride ions, carbonates, nitrates, sulfates and bicarbonates below 10 mM.

Citation Information

Patent Citations

  • A photocatalyst for activating sulfite to degrade tetracycline, its preparation method and application

    CN115155589B

  • MOFs-Co induced and derived Co-doped C3N5 photocatalyst as well as preparation method and application of MOFs-Co induced and derived Co-doped C3N5 photocatalyst

    CN117339632A